Prawo do decydowania o zakresie i zasięgu informacji udostępnianych innym osobom na temat swojego życia w kontekście Big Data - Grzymisławska-Cybulska, Maria; Cybulski, Marcin (Wydawnictwo Naukowe UAM, 2014)
The technological development and naturally fl owing from it possibilities of managing information generate increasing anxiety regarding the right to confi dentiality of private information and its protection. In this age of considerable technological progress combined with mass access to mobile applications, big data processing has become of particular signifi cance. A substantial economic signifi cance of data processing was also stressed in ordinance No. 157 of the Council of Ministers held on 25 September 2012 on the adoption of the Country’s Development Strategy 2020. Acknowledging the economic importance of big data processing, the Council of Ministers seemed to recognise the potential obstacles to its advancement due to still prevailing in Poland insuffi cient technological development, unsatisfactory equipment and mental resistance to change and novelty, and expressed doubts concerning aggregation and use of big data sets. Thus this paper aims to determine whether, and if, then what kind of threats may arise from the implementation of Big Data processing in Polish reality. In order to do that, the concept of Big Data needed first to be given a precise defi nition. Strangely enough, there is no such notion in Polish legal terminology despite the fact that the term has been used by central administrative bodies and theorists of the subject. Next the very issue of Big Data with a particular emphasis of the right to privacy and a guarantee of its protection is discussed. Since data protection derives from the protection of privacy, an attempt was also made to identify the current judicial problems related to personal data protection based on the analysis of the decisions delivered by the European Court of Human Rights, the Constitutional Court (Trybunał Konstytucyjny) and the Supreme Administrative Court (Naczelny Sąd Administracyjny) as well as regional administrative courts.
The right to decide upon the scope of information and the range of recipients personal data available to third parties in the context of the Big Data
Keywords: Big Data; big data base processing; right to privacy; data protection